2007
DOI: 10.2208/jsceje.63.66
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Random Cracks on the Shear Behavior of Reinforced Concrete Beams Containing Steel Fibers

Abstract: The present study is aimed at investigating the influence of random cracks on the shear behavior of RC beams with steel fibers. For this purpose, several amounts of expansion agent and two percentages of steel fibers were used. From the strain history during the curing period of time, some sort of chemical prestress could be observed due to the use of expansion agent. Random cracks were successfully created and the pattern showed different crack densities, defined as the ratio between the area of the cracks an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…Because ASR induced cracking takes a lot of time and special conditions to develop, the use of an expansion agent came as an alternative to have extensive cracking in a short period of time. From the results of previous research work 8) it was concluded that using expansion agents to generate distributed cracks in RC beams leads to a crack pattern similar to those obtained in actual structures 9) . The present study will further investigate the similarities between the two crack patterns.…”
Section: Research Motivationmentioning
confidence: 53%
See 4 more Smart Citations
“…Because ASR induced cracking takes a lot of time and special conditions to develop, the use of an expansion agent came as an alternative to have extensive cracking in a short period of time. From the results of previous research work 8) it was concluded that using expansion agents to generate distributed cracks in RC beams leads to a crack pattern similar to those obtained in actual structures 9) . The present study will further investigate the similarities between the two crack patterns.…”
Section: Research Motivationmentioning
confidence: 53%
“…Being randomly distributed throughout the concrete mass, steel fibers can better control the cracking in any direction. Adding short fibers to the concrete mix has several benefic effects ranging from reducing the crack opening 8) to an increase in the deformability and shear carrying capacity of RC beams 10), 11) .…”
Section: Research Motivationmentioning
confidence: 99%
See 3 more Smart Citations